INFLUENCE ANALYSIS OF BI RATE, INFLATION AND IHSG ON STOCK RETURN OF BANKING SECTOR LISTED ON INDONESIAN STOCK - Ferry Suwito (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2020)
This research aims to prove if there is any effect from the change of BI Rate, inflation, and IHSG to the return of banking sector listed in Indonesian Stock Exchange. Hypothesis is tested using multiple regression linear with monthly observation period during year 2007 – 2011 towards 12 banking stock return which are listed in Indonesia Stock Exchange. This research provides empirical evidence that simultaneously BI Rate, inflation and IHSG have effect on 9 stock return of banking sector, whereas partially tested IHSG has the most significant effect on stock return on banking companies compared with BI rate and inflation.